Influence of Compacting Rate on the Properties of Compressed Earth Blocks - Humphrey Danso (Advances in Materials Science and Engineering)
Compaction of blocks contributes significantly to the strength properties of compressed earth blocks. This paper investigates the influence of compacting rates on the properties of compressed earth blocks. Experiments were conducted to determine the density, compressive strength, splitting tensile strength, and erosion properties of compressed earth blocks produced with different rates of compacting speed. The study concludes that although the low rate of compaction achieved slightly better performance characteristics, there is no statistically significant difference between the soil blocks produced with low compacting rate and high compacting rate. The study demonstrates that there is not much influence on the properties of compressed earth blocks produced with low and high compacting rates. It was further found that there are strong linear correlations between the compressive strength test and density, and density and the erosion. However, a weak linear correlation was found between tensile strength and compressive strength, and tensile strength and density.